Teaching Model for Disaster Preparedness School Based Earthquake Prone Earthquake in Lombok - Dodik Kariadi; Enok Maryani; Helius Sjamsuddin; Mamat Ruhimat (JETL (Journal of Education, Teaching and Learning), 2020)
The problem in this research is that the teaching of school-based earthquake disaster preparedness in Lombok has not been optimal. In fact, the island of Lombok is an area with a high level of vulnerability to earthquakes. This is because one of them is the Flores Thrust which stretches from the eastern tip of the Flores Sea to the north of Bali. Thus in this study the main objective is to develop a preparedness teaching model for earthquake-prone schools. Where earthquake disaster preparedness is all efforts and activities carried out before a natural disaster occurs, during a disaster and immediately after a disaster to quickly and effectively respond to the situation or situation. The research method used is a research and development approach (Research & Development). The results showed several results including; First, the use of this preparedness teaching model shows that schools have more knowledge as a result of modeling in learning; Second, the exposure of the functions and responsibilities of one of the main leading sectors in disaster management; and The three resulting teaching models have simplified disaster management in schools because they are integrated with Social Science learning so that they are easily realized. So with the model of teaching student preparedness it will be more effective and efficient in order to improve their ability to face earthquakes that can occur at any time.